Alkali metal bifunctional catalyst-sorbents enabled biomass pyrolysis for enhanced hydrogen production. (April 2020) - Zhao, Ming; Memon, Muhammad Zaki; Ji, Guozhao; Yang, Xiaoxiao; Vuppaladadiyam, Arun K.; Song, Yinqiang; Raheem, Abdul; Li, Jinhui; Wang, Wei; Zhou, Hui
Abstract: Alkali ceramics are well-known high temperature CO2 sorbents in forms of zirconates or orthosilicates with catalytic tar cracking ability prior to or after carbonation. In this study, Li2 ZrO3, Li4 SiO4, and Na2 ZrO3 were selected as catalyst-sorbent bifunctional materials to enhance the pyrolysis of sawdust. This study investigated the synergy between the alkali metal bifunctional materials under pyrolytic conditions. The weight loss data and gas yield trends in the temperature between 200 and 800 °C demonstrated a combined catalytic process and gas-solid reaction. A metal carbonate phase was formed after the reaction of capturing CO2 . The CO2 capture promoted H2 production because of Le Chatelier principle and the formation of carbonate phase assisted tar cracking reactions. H2 production increased from 5.73 mmol g −1 to 8.87 mmol g −1, 15.85 mmol g −1, and 13.67 mmol g −1 in the presence of Li2 ZrO3, Li4 SiO4, and Na2 ZrO3, respectively. At temperatures around 700 °C, CO was released due to secondary cracking reaction and the Boudouard reaction of CO2 released from the sorbents. Overall, the alkali ceramics present the catalyst-sorbent bifunctional activity for enhancing H2 production during biomass pyrolysis. Graphical abstract: Image 100066 Highlights: Bifunctional catalyst-sorbent activity of alkali ceramics was investigated. Alkali ceramics were active in catalytic and chemisorption activities of pyrolysis. Presence of alkali ceramics increased H2 yield by two-fold. At 700 °C alkali ceramics participated in gasification of char.